A Personalist Approach to the Just Allocation of Resources in the Midst of a Pandemic - Johnny Sakr (Philosophies)
This paper examines the ethical implications of healthcare resource allocation during the first wave of COVID-19 in Italy, from 21 February to 31 May 2020, with a focus on the utilitarian principles that prioritized age-based resource allocation. By comparing this approach to an ontological personalist bioethics framework, the study aims to offer a more equitable strategy for healthcare allocation applicable to any pandemic. Data from governmental reports, healthcare policies, and ethical guidelines were analyzed, revealing that Italy’s utilitarian method led to significant ethical concerns, particularly regarding age discrimination. In contrast, the ontological personalist approach emphasizes the dignity and intrinsic worth of each individual, irrespective of age or health condition. The findings demonstrate that this personalist framework fosters a more balanced and fair allocation of resources, respecting human dignity and offering a universally applicable alternative to age-based prioritization. Ultimately, the study suggests that integrating ontological personalist principles into healthcare policies could enhance ethical decision-making in future pandemics, ensuring that resource allocation practices align more closely with human rights and individual dignity.